CRITICAL ANALYSIS OF THE RELIABILITY OF INTUITIVE MORAL DECISIONS - V. V. Nadurak (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the research is a critical analysis of the reliability of intuitive moral decisions. Methodology. The work is based on the methodological attitude of empirical ethics, involving the use of findings from empirical research in ethical reflection and decision making. Originality. The main kinds of intuitive moral decisions are identified: 1) intuitively emotional decisions (i.e. decisions made under the influence of emotions that accompanies the process of moral decision making); 2) decisions made under the influence of moral risky psychological aptitudes (unconscious human tendencies that makes us think in a certain way and make decisions, unacceptable from the logical and ethical point of view); 3) intuitively normative decisions (decisions made under the influence of socially learned norms, that cause evaluative feeling «good-bad», without conscious reasoning). It was found that all of these kinds of intuitive moral decisions can lead to mistakes in the moral life. Conclusions. Considering the fact that intuition systematically leads to erroneous moral decisions, intuitive reaction cannot be the only source for making such decisions. The conscious rational reasoning can compensate for weaknesses of intuition. In this case, there is a necessity in theoretical model that would structure the knowledge about the interactions between intuitive and rational factors in moral decisions making and became the basis for making suggestions that would help us to make the right moral decision.